2018
DOI: 10.1371/journal.pone.0195608
|View full text |Cite
|
Sign up to set email alerts
|

Second course of stereotactic radiosurgery for locally recurrent brain metastases: Safety and efficacy

Abstract: In the present study, we have evaluated the efficacy and toxicity of repeated brain metastases (BM) stereotactic radiosurgery (SRS2) following local failure of a prior radiosurgical procedure (SRS1). Between December 1996 and August 2015, 30 patients with 36 BM underwent SRS2 with a median dose of 18Gy. All BM were located outside critical structures. Following SRS2, local control at 6 months and one year were respectively 82.9% (IC 95%: 67.6–91.9) and 67.8% (IC 95%: 51–81). On multivariate analysis, planning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 34 publications
1
36
0
5
Order By: Relevance
“…13 With reported 12month progression rates of 27.2% for unoperated 6 and 40% for resected BMs 5 after SRS, repeat irradiation is anticipated to be an increasingly used salvage therapy in this setting. 14,15 Combined with a reported occurrence of RN after initial SRS of 16% at 12 months with a plateaus at nearly 40% by 40 months, 7 these observations indicate that delineating recurrent tumor from RN in previously treated BM patients will become a more common clinical scenario. This distinction is of particular importance for clinical decision-making given that recurrent tumor can be effectively treated by reirradiation as noted earlier, or in the case of radiation necrosis, by other modalities such as laser interstitial thermal therapy.…”
Section: Discussionmentioning
confidence: 98%
“…13 With reported 12month progression rates of 27.2% for unoperated 6 and 40% for resected BMs 5 after SRS, repeat irradiation is anticipated to be an increasingly used salvage therapy in this setting. 14,15 Combined with a reported occurrence of RN after initial SRS of 16% at 12 months with a plateaus at nearly 40% by 40 months, 7 these observations indicate that delineating recurrent tumor from RN in previously treated BM patients will become a more common clinical scenario. This distinction is of particular importance for clinical decision-making given that recurrent tumor can be effectively treated by reirradiation as noted earlier, or in the case of radiation necrosis, by other modalities such as laser interstitial thermal therapy.…”
Section: Discussionmentioning
confidence: 98%
“…We identified and reviewed six retrospective clinical studies of sequential WBRT and two courses of SRT [14-19]. Balermpas et al reported on 31 patients with 32 recurrent brain metastases (31% each with breast and non-small cell lung cancer [NSCLC]) [14].…”
Section: Reviewmentioning
confidence: 99%
“…Moreau et al [19] have published the largest dataset of interest ( n = 24), extracted from their analysis of 30 patients with 36 lesions (50% lung cancer, not stratified by histology). None of the patients had a neurological deficit at the time of second SRS.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Today, focused methods such as SRS are more attractive in patients with oligometastatic brain metastases while WBRT is reserved for patients with higher burdens of intracranial disease [ 7 ]. SRS significantly limits the exposure of healthy brain tissue while delivering high doses of therapeutic radiation within a short period of time [ 8 ]. However, WBRT and SRS are both hampered by known complications in treating brain lesions.…”
Section: Introductionmentioning
confidence: 99%